Legal Issues and Policy Improvement Measures Regarding the Use of Medical Devices by Korean Medicine Doctors: A Comparative Study of Japan, China, and the United States - Junchul Kang (Journal of Korean Medicine, 2026)
Objectives: This study examines the legal ambiguity and policy challenges surrounding the use of medical devices by Korean medicine doctors within Korea’s dual medical system. It seeks to clarify unresolved issues related to scope of practice and to propose institutional reforms through a systematic analysis of judicial precedents and comparative health law frameworks.Methods: A doctrinal legal analysis was conducted focusing on domestic judicial precedents concerning the use of medical devices by Korean medicine doctors, with particular emphasis on the Supreme Court of Korea’s en banc decision (Case No. 2016Do21314). Relevant lower court rulings and administrative interpretations were reviewed to identify prevailing legal standards. In addition, a comparative analysis of legislative and regulatory systems in Japan, China, and the United States was performed to examine how these jurisdictions define scope of practice, qualification requirements, and permissible medical device usage. Based on these findings, policy alternatives were derived through comparative health policy analysis.Results: The findings indicate that recent judicial decisions have partially recognized the permissibility of certain medical device usage by Korean medicine doctors; however, the Medical Service Act lacks explicit statutory provisions governing this issue. Consequently, legal determinations remain dependent on judicial interpretation and administrative discretion, thereby intensifying interprofessional conflicts. In contrast, the comparative analysis demonstrates that other jurisdictions maintain clearer and more systematic regulatory frameworks.Conclusions: This study calls for comprehensive legislative and policy reforms including statutory amendments, education-based qualification standards, risk-based authorization, and collaborative frameworks to enhance patient safety and public health.